Imago and contemplatio in the visual arts and literature (1400-1700): Festschrift for Walter S. Melion - Bussels, Stijn (Intersections, 2024)
"This volume contains twenty-four essays, which, in their subjects and methodology, pay tribute to the scholarship of Walter S. Melion. The contributions are grouped under three categories: "Devotion", "Art and Image Theory", and "Vision and Contemplation". The Devotion section addresses votive practices, theological theory and polemic literature. The Art and Image Theory section focuses on Jesuit image theory, the reflexive dimension of works, and artists' reflections on the function of images. Finally, the Vision and Contemplation section discusses the 'early modern eye' as a tool for thoughtful, prolonged looking to ascertain visual wit, deception, self-assessment and friendship, sacred and profane allegories."
Keywords: Festschrift; Geschichte 1400-1700; Erbauungsliteratur; Andachtsbild; Melion, Walter S.